The Castaway is Building a Boat. An Overview of Robinson Crusoe’s Reception Threads in the Narrations of Holocaust Survivors - Roszak, Joanna (Porównania, 2019)
The author of the article attempts to review selected reception threads of Daniel Defoe’s The Life and Strange Surprising Adventures of Robinson Crusoe (1719) in connection to the Holocaust. Thus, it is shown what elements of the novel are updated in the context of the Shoah, which are blurred, and what this three hundred year old book has to say about the fate of other books and people of the 20th century. The English novel is used in the interpreted texts as a synecdoche (Primo Levi, Uri Orlev), apotropaic reading (personal testimonies, including memories of Hanke Grynberg) or the basis for creating apocrypha (poems by Dan Pagis and Jehuda Amichaj).